The Role of Data Science in Optimizing Business Decisions in the Digital Era - Samudra, Dewa; Ulya, Annisa Zulfa; Sulitiani, Heni (LPPM STIKI Malang, 2024)
Data science has become a key element in business transformation in the digital era. With the ability to analyze large and diverse datasets, data science helps organizations identify patterns, make predictions, and support strategic decision-making. The application of technologies such as machine learning, big data, and artificial intelligence enables companies to enhance operational efficiency, understand consumer behavior, and create relevant innovations. This article discusses the role of data science in supporting the growth of digital businesses, the challenges faced, and the opportunities companies can leverage to achieve a competitive advantage.